Recognition across Axel Honneth and Paul Ricoeur: Making a Case for Solicitude - Krishnaswamy, R. (Sophia, 2025)
In this article, my aim is to review the idea of solidarity within Axel Honneth's theory of recognition and critique it using Ricoeur's view of recognition. Honneth's notion of solidarity though is able to help us solve and explain certain important aspects of our socio-political life, I will show that a solidaristic form of recognition can't fully help us produce a society where every person feels necessarily dignified and works with self-esteem which is generated out of social interaction. In Axel Honneth's framework, as Honneth himself acknowledges, there is always a struggle for recognition. I will show why or how that struggle for recognition is bound to produce moments of mis-recognition where some people within a community lack dignity. I will then juxtapose Paul Ricoeur's idea of recognition which can help solve this problem of social dissonance. Ultimately, I will point to how within Ricoeur's conception, there need not be any struggles for recognition but only states of peace where people establish a relation of mutuality between each other which is both expressive of each person's self-esteem as well as grounded in the recognition of a person’s freedom to express themselves without any external constraints.